Establishment of a stable sampling method to assay mercaptoalbumin/non-mercaptoalbumin and reference ranges - Yasukawa, Keiko (Pract Lab Med, 2019)
Oxidative stress is reportedly associated with many diseases such as cancer, arteriosclerosis, diabetes and aging, but no practical biomarkers are currently available in actual clinical practice. Human mercaptoalbumin (HMA) and human non-mercaptoalbumin (HNA) are expected to become markers of oxidative stress, but the stability of HMA/HNA has been problematic. We investigated the conditions for stabilizing HMA/HNA and found that HMA/HNA was stable at room temperature for 25 h if whole blood samples were mixed with a citrate buffer so that the citric acid concentration after mixing was 70 mM or higher and the pH of the added buffer was less than pH 6.0. Whole blood samples were then collected under the above conditions, and the reference range for HNA was set at 21.8% ± 7.4% (HMA, 78.2% ± 7.4%) based on samples from 65 volunteers (28 males and 37 females; average age, 55.0 ± 13.8 years). The clinical usefulness of HMA/HNA as an oxidative stress marker should be clarified for specific pathological conditions using the previously reported, highly accurate measurement method under the conditions required for HMA/HNA stability.